PENYESUAIAN DIRI MAHASISWA PADA ADAT DAN BUDAYA MASYARAKAT DESA GADING JAYA KECAMATAN TABIR SELATAN KABUPATEN MERANGIN PROVINSI JAMBI: Adat Budaya Desa - hapid alatas, uying hapid; Fithri Azni; Aksul Dewi Fikra; Iswandi; Henky Setiadi; Diyan Andriani; Sri Utami; Sukur (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2025)
This study aims to determine 1) students' self-adjustment to community culture, 2) Obstacles faced by students in the process themselves with the cultural adjustment of society. The research method used is a qualitative descriptive method. Data collection techniques using observation. Research results based on data analysis shows 1) Student self-adjustment to society is classified as not good at adapting. Student self-adjustment to the culture of society which is classified as not good evidenced through five indicators consisting of two dimensions. From fifth Of these indicators, only two of them were able to be fulfilled by students while carrying out the real work lecture process. 2) Adjustment constraints students in the process of adjusting to the culture of society are also not good. In this case, students in overcoming obstacles of self-adjustment do not can overcome all the obstacles that exist in adaptation to the culture of the community is proven by four indicators of adjustment constraints self is only one that can be overcome by students. Keywords: Self-adjustment, Student, Community Culture, Gading Jaya Village of South Tabir, Merangin University.